A sensitivity comparison of the Quick and Owren prothrombin time methods in oral anticoagulant therapy - Horsti, Juha (PAGEPress Publications, 2009)
Prothrombin time (PT) is the leading test for monitoring oral anticoagulation therapy (OAT). According to the World Health Organization recommendation, International Normalized Ratio (INR) results obtained from the same patient samples with the major PT methods (Quick and Owren) should be the same when the therapeutic range is the same. In our study blood samples were obtained from 207 OAT patients. We analyzed the samples using two Quick and two Owren PT (combined thromboplastin) reagents for INR and assessed the sensitivity and true coagulation activity using a new-generation PT method. The INR values with the Quick PT and Owren PT methods were very similar around the normal range, while unacceptable differences were seen within the therapeutic range and at higher INR values. The Quick PT results as INR are clearly lower than those given by Owren PT and the difference increases toward higher INR. The new PT method functions well with both Owren PT reagents, and we can calculate the true active INR. The Quick PT methods show no sensitivity to coagulation inhibition measurement. The harmonization of the INR is an important goal for the safety of OAT patients. More accurate INR results reduce morbidity and mortality, and the therapeutic ranges should be similar worldwide. In this study we found unacceptable differences in INR results produced by the two PT methods. The new method showed a lack of sensitivity to Quick PT. For the global harmonization of OAT therapy and for INR accuracy only the more sensitive Owren PT method should be used.